2023
DOI: 10.1007/s00330-023-10215-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantification of perfusion, permeability, and leakage effects in brain gliomas using dynamic spin-and-gradient-echo echoplanar imaging MRI

Francesco Sanvito,
Catalina Raymond,
Nicholas S. Cho
et al.

Abstract: Objective To determine the feasibility and biologic correlations of dynamic susceptibility contrast (DSC), dynamic contrast enhanced (DCE), and quantitative maps derived from contrast leakage effects obtained simultaneously in gliomas using dynamic spin-and-gradient-echo echoplanar imaging (dynamic SAGE-EPI) during a single contrast injection. Materials and methods Thirty-eight patients with enhancing brain gliomas were prospectively imaged with dynamic SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…As we have shown that practical identifiability improves with increasing SNR, we emphasize the need for image acquisition standards to increase the quality of imaging data and therefore reliability of parameter estimations such as the standards proposed by the Quantitative Imaging Biomarkers Alliance (QIBA) [ 75 ]. As DCE-MRI acquisition protocols and quantification methods continue to rapidly develop [ 76 ], it is important to ensure rigor in model fitting and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…As we have shown that practical identifiability improves with increasing SNR, we emphasize the need for image acquisition standards to increase the quality of imaging data and therefore reliability of parameter estimations such as the standards proposed by the Quantitative Imaging Biomarkers Alliance (QIBA) [ 75 ]. As DCE-MRI acquisition protocols and quantification methods continue to rapidly develop [ 76 ], it is important to ensure rigor in model fitting and analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of post-bolus to pre-bolus DSC signal intensity, as measured with the percentage of signal recovery (PSR), is thought to be influenced by tissue microstructure, and therefore useful for differential diagnosis ( 65 , 79 ). Post-bolus signal intensity is influenced by the balance between T 2 * and T 1 leakage effects, which has been suggested to reflect tissue cytoarchitecture ( 77 , 80 , 81 ). PSR utility has been demonstrated in the diagnostic phase rather than in treatment response monitoring so far, thus its evaluation may not be directly relevant for clinical trials at the moment.…”
Section: Rationale Behind Btip Sequences and Technical Considerationsmentioning
confidence: 99%
“…DCE maps reflect the contrast leakage characteristics. In this case, DCE metrics were obtained simultaneously with DSC, using a dynamic spin-and-gradient-echo perfusion sequence as described in ( 81 ). Finally, sodium images were obtained at the end of the protocol and sodium signal voxel-wise was normalized to the eye sodium signal.…”
Section: Integration Of Additional Sequencesmentioning
confidence: 99%
“… 24–27 While there do exist MRI sequences which directly measure interstitial fluid velocity, they struggle with separating vascular flow from interstitial flow and require additional imaging sequences to be applied, significantly increasing the time a patient spends in the scanner. 28,29 Given that DCE-MRI is becoming a standard clinical practice and novel methods for its acquisition are being actively developed, 30 there is growing opportunity to utilize it for studying interstitial flow, without the need for requiring more time in the scanner.…”
Section: Introductionmentioning
confidence: 99%